PERFORMANCE OF A SOLAR PAPER DRIER FOR SMALL-SCALE PAPER SHEET PRODUCTION - Hjort, Mikael; Thomas, Daniel E. (Journal of Mechanical Engineering, 2014)
This study was conducted to evaluate the performance of a paper drier operating on solar-heated hotwater. A small-scale prototype of a flat tank paper drier was built and tested in a variety of conditions and witha variety of handmade paper types. The tests showed consistent performance, with a specific energyconsumption of about 3.5 MJ per kg of water evaporated from the paper. This corresponds to a drier efficiencyof up to 80%, with reference to the latent heat of evaporation. Drier temperature variations were minimal, andthe performance was considered satisfactory to continue with further development of the drier for localhandmade paper production facilities. Measured drying rates compared well with predicted values calculatedusing correlations based on Stefan's law. DOI: http://dx.doi.org/10.3329/jme.v44i1.19491